Implementasi Aplikasi E-UMKM pada Beni Scroll Art - Triana Sri Gunarti; Baibul Tujni; Imam Solikin Imam Solikin (Politeknik Caltex Riau, 2022)
Micro, Small and Medium Enterprises (MSMEs) are micro businesses that are productive in their activities, and are owned by business entities or individuals. MSMEs at Beni Scroll Art (BSA) are engaged in handicrafts. The process of marketing, selling and buying that occurs in BSA MSMEs is still happening conventionally, between sales and consumers must meet directly physically. Activities that occur conventionally cause sales to be obedient, because many other competitors are selling online, making it easier to process transactions and consumers prefer digital transaction processes. Another problem that arises from the conventional process is that the process of promoting goods is not too broad because the promotion process can only be carried out in affordable areas. The solution to overcome this problem is that BSA MSMEs need to develop a marketing and buying and selling system by utilizing digital technology, namely building a BSA E-UMKM application that can be accessed online. E-UMKM BSA is an application that can be used to facilitate marketing and buying and selling transactions because it can be accessed online without meeting face to face. E-UMKM BSA can promote goods widely without having to do it physically. The waterfall method is a method used to assist in the development of the BSA E-UMKM application. The purpose of building E-UMKM BSA is to expand the range of promotions and increase sales of goods.